Burned area mapping across the Arctic-boreal zone with Landsat and Sentinel-2 imagery - Stefano Potter; Yili Yang; Arden Burrell; Anna Talucci; Andrew A. Clelland; Sander Veraverbeke; James T. Randerson; Scott J. Goetz; Logan T. Berner; Michelle C. Mack; Xanthe J. Walker; Susan M. Natali; et al. (International Journal of Remote Sensing, 2026)

Cook Inlet beluga whale calling varies by group characteristics, behavior, and tidal state - Arial M. Brewer; Amy M. Van Cise; Christopher Garner; Andrea Gilstad; Manuel Castellote; Sarah J. Converse; Kimberly T. Goetz; Andrew M. Berdahl (Behavioral Ecology and Sociobiology, 2026)
Communication allows social species to exchange information among group members. In aquatic environments, acoustic signals are among the most effective forms of communication and are important for many species, including cetaceans. Beluga whales ( Delphinapterus leucas ) are highly social and vocal, yet little is known about the functionality of their social calls. To examine context-dependent vocal behavior in belugas, we collected passive acoustic data and fine-scale behavioral observations for the endangered Cook Inlet beluga population. The resulting dataset includes 1,720 annotated vocalizations collected over 21 behaviorally encoded encounters. We fit generalized linear mixed models to these data to investigate the effect of behavioral state, group size, calf presence, and tidal state on (1) calling rate (number of calls/minute) and (2) call category (whistles, pulsed calls, combined calls). Belugas were more likely to call when traveling and had higher calling rates during flood tides. Group-level calling rate increased sublinearly with group size, suggesting that individuals called less in larger groups, possibly reflecting increased listening, vocal coordination, or a strategy to avoid acoustic masking. Group calling rate increased before transitions between traveling and milling, suggesting a possible link between communication and behavioral transitions. Whistles were more prevalent when traveling, while pulsed calls were more prevalent when milling. Combined calls occurred only when calves were present, indicating the importance of these calls in communication with calves. Identifying these communication patterns and the contexts in which they occur can enhance our understanding of beluga whale ecology and aid in conservation efforts via passive acoustic monitoring.

Contribution of biotechnology to attaining UN Sustainable Development Goals (SDGs) – I - Sergio Ochatt; Barbara Doyle Prestwich; Goetz Hensel; Patricia Marconi; M. Margarida Oliveira; Wagner Otoni; Bart Panis (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Mothers know best: Maternal signaling boosts larval resilience under ocean acidification conditions - Emma Timmins-Schiffman; Larken Root; Ryan Crim; Mollie A. Middleton; Megan M. Ewing; Jacob Winnikoff; Gracelyn Ham; Giles Goetz; Steven Roberts; Mackenzie R. Gavery (Aquaculture, 2026)

High meiofaunal diversity in the Azores revealed through DNA metabarcoding - Francesca Leasi; Nuno V. Álvaro; Luiz F. Andrade; Thiago Q. Araújo; Víctor Aramayo; Tom Artois; Will M. Ballentine; Franziska S. Bergmeier; Andrea Z. Botelho; Ariane Buckenmeyer; Ana T. Capucho; Irina Cherneva; et al. (Marine Biodiversity, 2026)
To advance understanding of meiofauna, key components of marine benthic ecosystems, an international team conducted a morphology-based taxonomic survey and workshop around São Miguel, the largest Azorean island, in 2019. The survey yielded critical baseline data on meiofaunal diversity and, despite taxonomic challenges that limited identification of certain taxa, laid a solid foundation for further research. To expand these findings, additional samples were analyzed using DNA metabarcoding, a powerful tool that assesses multiple facets of biodiversity, including richness, community composition, and phylogenetic diversity. Metabarcoding identified 480 meiofaunal amplicon sequence variants across 14 phyla, more than doubling the 180 taxa recorded through morphology alone. Of these, 298 (approximately 62%) belonged to phyla targeted during the morphology-based workshop. A comparison between the two approaches, focusing on clades addressed during the workshop, revealed overlapping but expanded patterns of diversity relative to morphology-based taxonomy. This consistency supports the metabarcoding’s ability to uncover meiofaunal diversity and underscores the importance of integrating both methods to achieve a more comprehensive understanding of biodiversity and ecological patterns. As the first metabarcoding study in the Azores, this work establishes a biodiversity baseline for a remote and understudied region, indicating greater benthic diversity than previously recognized. By revealing the complexity of these understudied ecosystems, this research contributes to document and support conservation of biodiversity in the Azores and emphasizes the need for further exploration of meiofaunal communities in isolated oceanic environments.

Next generation Arctic vegetation maps: Aboveground plant biomass and woody dominance mapped at 30 m resolution across the tundra biome - Kathleen M. Orndahl; Logan T. Berner; Matthew J. Macander; Marie F. Arndal; Heather D. Alexander; Elyn R. Humphreys; Michael M. Loranty; Sarah M. Ludwig; Johanna Nyman; Sari Juutinen; Mika Aurela; Juha Mikola; et al. (Remote Sensing of Environment, 2025)

Amendment effectiveness and seasonal variations in a lead contaminated acidic wetland - Matthew R. Noerpel; Anna M. Wade; Aaron R. Betts; Jennifer Goetz; Robert Ford; Amy Krause; Michael Zeolla; Diana Cutt; Stephanie M. Wilson; Todd P. Luxton (Applied Geochemistry, 2025)

Using eDNA to Supplement Population Genetic Analyses for Cryptic Marine Species: Identifying Population Boundaries for Alaska Harbour Porpoises - Kim M. Parsons; Samuel A. May; Zachary Gold; Marilyn Dahlheim; Christine Gabriele; Janice M. Straley; John R. Moran; Kimberly Goetz; Alexandre N. Zerbini; Linda Park; Phillip A. Morin (Molecular Ecology, 2025)
Isolation by distance and biogeographical boundaries define patterns of population genetic structure for harbour porpoise along the Pacific coast from California to British Columbia. Until recently, inadequate sample sizes in many regions constrained efforts to characterise population genetic structure throughout the coastal waters of Alaska. Here, tissue samples from beachcast strandings and fisheries bycatch were supplemented with targeted environmental DNA (eDNA) samples in key regions of Alaska coastal and inland waters. Using a geographically explicit, hierarchical approach, we examined the genetic structure of Alaska harbour porpoises, using both mitochondrial DNA (mtDNA) sequence data and multilocus SNP genotypes. Despite a lack of evidence of genetic differentiation from nuclear SNP loci, patterns of relatedness and genetic differentiation from mtDNA suggest natal philopatry at multiple geographic scales, with limited gene flow among sites possibly mediated by male dispersal. A priori clustering of sampled areas at an intermediate scale (eastern and western Bering Sea, Gulf of Alaska and Southeast Alaska) best explained the genetic variance (12.37%) among regions. In addition, mtDNA differentiation between the Gulf of Alaska and eastern Bering Sea, and among regions within the Gulf of Alaska, indicated significant genetic structuring of harbour porpoise populations in Southeast Alaska. The targeted collection of eDNA samples from strata within Southeast Alaska was key for elevating the statistical power of our mtDNA dataset, and findings indicate limited dispersal between neighbouring strata within coastal and inland waters. These results provide evidence supporting a population boundary within the currently recognised Southeast Alaska Stock. Together, these findings will prove useful for ongoing management efforts to reduce fisheries conflict and conserve genetic diversity in this iconic coastal species.

Mobilization of porewater Pb and Zn in response to seasonal wetting and drying within contaminated floodplains - Anna M. Wade; Chris S. Eckley; Matthew Noerpel; Jennifer Goetz; David Leptich; Kim Prestbo; David Van de Riet; Steve Sluka; Richard Wilkin; Todd P. Luxton (Science of The Total Environment, 2025)

High thermal quality rookeries facilitate high thermoregulatory accuracy in pregnant female rattlesnakes - Haley A. Moniz; Jack H. Buck; Hayley L. Crowell; Scott M. Goetz; Trevor D. Ruiz; Emily N. Taylor; Scott M. Boback (Journal of Thermal Biology, 2024)

Aspects of the biological carbon cycle in a ca. 3.42-billion-year-old marine ecosystem - M. Reinhardt; V. Thiel; J.-P. Duda; A. Hofmann; D. Bajnai; W. Goetz; A. Pack; J. Reitner; M. Schanofski; J. Schönig; M.J. Whitehouse; H. Drake (Precambrian Research, 2024)

Movements of anadromous coastal cutthroat trout (Oncorhynchus clarkii clarkii) in Puget Sound, Washington, USA - Thomas P. Quinn; Martin C. Arostegui; Christopher S. Ellings; Frederick Goetz; James P. Losee; Joseph M. Smith; Sarah R. Zaniewski (Environmental Biology of Fishes, 2024)

The unique floor of Juling crater on Ceres - J. Hernandez; A. Nathues; H. Hiesinger; R. Sarkar; M. Hoffmann; W. Goetz; G. Thangjam (Planetary and Space Science, 2023)

Shifts in Ecological Legacies Support Hysteresis of Stand Type Conversions in Boreal Forests - X. J. Walker; K. Okano; L. T. Berner; R. Massey; S. J. Goetz; J. F. Johnstone; M. C. Mack (Ecosystems, 2023)

Bioenergy crop production and carbon sequestration potential under changing climate and land use: A case study in the upper River Taw catchment in southwest England - Prakash N. Dixit; Goetz M. Richter; Kevin Coleman; Adrian L. Collins (Science of The Total Environment, 2023)

Decadal impacts of wildfire fuel reduction treatments on ecosystem characteristics and fire behavior in alaskan boreal forests - Melissa A. Boyd; Xanthe J. Walker; Jennifer Barnes; Gerardo Celis; Scott J. Goetz; Jill F. Johnstone; Nicholas T. Link; April M. Melvin; Lisa Saperstein; Edward A.G. Schuur; Michelle C. Mack (Forest Ecology and Management, 2023)

The role of biotechnological tools for mitigating abiotic stress in a changing climate – preface - Sergio J. Ochatt; Amita Bhattacharya; Barbara M. Doyle Prestwich; Christophe Hano; Goetz Hensel; Patricia L. Marconi; Christell Van der Vyver (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Carbon uptake in Eurasian boreal forests dominates the high‐latitude net ecosystem carbon budget - Jennifer D. Watts; Mary Farina; John S. Kimball; Luke D. Schiferl; Zhihua Liu; Kyle A. Arndt; Donatella Zona; Ashley Ballantyne; Eugénie S. Euskirchen; Frans‐Jan W. Parmentier; Manuel Helbig; Oliver Sonnentag; et al. (Global Change Biology, 2023)
Arctic‐boreal landscapes are experiencing profound warming, along with changes in ecosystem moisture status and disturbance from fire. This region is of global importance in terms of carbon feedbacks to climate, yet the sign (sink or source) and magnitude of the Arctic‐boreal carbon budget within recent years remains highly uncertain. Here, we provide new estimates of recent (2003–2015) vegetation gross primary productivity (GPP), ecosystem respiration ( R eco ), net ecosystem CO 2 exchange (NEE; R eco − GPP), and terrestrial methane (CH 4 ) emissions for the Arctic‐boreal zone using a satellite data‐driven process‐model for northern ecosystems (TCFM‐Arctic), calibrated and evaluated using measurements from >60 tower eddy covariance (EC) sites. We used TCFM‐Arctic to obtain daily 1‐km 2 flux estimates and annual carbon budgets for the pan‐Arctic‐boreal region. Across the domain, the model indicated an overall average NEE sink of −850 Tg CO 2 ‐C year −1 . Eurasian boreal zones, especially those in Siberia, contributed to a majority of the net sink. In contrast, the tundra biome was relatively carbon neutral (ranging from small sink to source). Regional CH 4 emissions from tundra and boreal wetlands (not accounting for aquatic CH 4 ) were estimated at 35 Tg CH 4 ‐C year −1 . Accounting for additional emissions from open water aquatic bodies and from fire, using available estimates from the literature, reduced the total regional NEE sink by 21% and shifted many far northern tundra landscapes, and some boreal forests, to a net carbon source. This assessment, based on in situ observations and models, improves our understanding of the high‐latitude carbon status and also indicates a continued need for integrated site‐to‐regional assessments to monitor the vulnerability of these ecosystems to climate change.

A Biologist’s Guide to the Galaxy: Leveraging Artificial Intelligence and Very High-Resolution Satellite Imagery to Monitor Marine Mammals from Space - Christin B. Khan; Kimberly T. Goetz; Hannah C. Cubaynes; Caleb Robinson; Erin Murnane; Tyler Aldrich; Meredith Sackett; Penny J. Clarke; Michelle A. LaRue; Timothy White; Kathleen Leonard; Anthony Ortiz; et al. (Journal of Marine Science and Engineering, 2023)
Monitoring marine mammals is of broad interest to governments and individuals around the globe. Very high-resolution (VHR) satellites hold the promise of reaching remote and challenging locations to fill gaps in our knowledge of marine mammal distribution. The time has come to create an operational platform that leverages the increased resolution of satellite imagery, proof-of-concept research, advances in cloud computing, and machine learning to monitor the world’s oceans. The Geospatial Artificial Intelligence for Animals (GAIA) initiative was formed to address this challenge with collaborative innovation from government agencies, academia, and the private sector. In this paper, we share lessons learned, challenges faced, and our vision for how VHR satellite imagery can enhance our understanding of cetacean distribution in the future.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Data Quality Influences the Predicted Distribution and Habitat of Four Southern-Hemisphere Albatross Species - Kimberly T. Goetz; Fabrice Stephenson; Andrew Hoskins; Aidan D. Bindoff; Rachael A. Orben; Paul M. Sagar; Leigh G. Torres; Caitlin E. Kroeger; Lisa A. Sztukowski; Richard A. Phillips; Stephen C. Votier; Stuart Bearhop; et al. (Frontiers in Marine Science, 2022)
Few studies have assessed the influence of data quality on the predicted probability of occurrence and preferred habitat of marine predators. We compared results from four species distribution models (SDMs) for four southern-hemisphere albatross species, Buller’s ( Thalassarche bulleri ), Campbell ( T. impavida ), grey-headed ( T. chrysostoma ), and white-capped ( T. steadi ), based on datasets of differing quality, ranging from no location data to twice-daily locations of individual birds collected by geolocation devices. Two relative environmental suitability (RES) models were fit using minimum and maximum preferred and absolute values for each environmental variable based on (1) monthly 50% kernel density contours and background environmental data, and (2) primary literature or expert opinion. Additionally, two boosted regression tree (BRT) models were fit using (1) opportunistic sightings data, and (2) geolocation data from bird-borne electronic tags. Using model-specific threshold values, habitat was quantified for each species and model. Model variables included distance from land, bathymetry, sea surface temperature, and chlorophyll- a concentration. Results from both RES models and the BRT model fit with opportunistic sightings were compared to those from the BRT model fit using geolocation data to assess the influence of data quality on predicted occupancy and habitat. For all species, BRT models outperformed RES models. BRT models offer a predictive advantage over RES models by being able to identify relevant variables, incorporate environmental interactions, and provide spatially explicit estimates of model uncertainty. RES models resulted in larger, less refined areas of predicted habitat for all species. Our study highlights the importance of data quality in predicting the distribution and habitat of albatrosses and emphasises the need to consider the pros and cons associated with different levels of data quality when using SDMs to inform management decisions. Furthermore, we examine the overlap in preferred habitat predicted by each SDM with fishing effort. We discuss the influence of data quality on predicting the wide-scale distributions of pelagic seabirds and how these impacts could result in different protection measures.

Crary bank: a deep foraging habitat for emperor penguins in the western Ross Sea - G. L. Kooyman; K. Goetz; C. L. Williams; P. J. Ponganis; K. Sato; S. Eckert; M. Horning; P. T. Thorson; R. P. Van Dam (Polar Biology, 2020)

Testing for hybridisation of the Critically Endangered Iguana delicatissima on Anguilla to inform conservation efforts - Kieran C. Pounder; F. Mukhida; R. P. Brown; D. Carter; J. C. Daltry; T. Fleming; M. Goetz; L. G. Halsey; G. Hughes; K. Questel; I. J. Saccheri; R. Williams; et al. (Conservation Genetics, 2020)
The Caribbean Island of Anguilla in the north-eastern Lesser Antilles is home to one of the last populations of the Critically Endangered Lesser Antillean iguana Iguana delicatissima . This population is highly threatened primarily because of hybridisation with non-native Iguana iguana . This study assesses the degree of hybridisation between Anguilla’s Iguana species firstly using morphological characteristics and then genetic analysis to validate the genetic integrity of morphologically identified I. delicatissima . We also examined the genetic diversity of Anguilla’s I. delicatissima population, and that of a population on the nearby island of Îlet Fourchue, St Barthélemy. Forty-five iguanas were captured in Anguilla and 10 in St Barthélemy, and sequences from 3 nuclear and 1 mtDNA genes were obtained for each. Of the 45 iguanas captured in Anguilla, 22 were morphologically identified as I. delicatissima , 12 as I. iguana and the remainder were identified as hybrids. Morphological assignments were all confirmed by genetic analyses except for one I. iguana and one hybrid individual. These two individuals appeared likely to have originated following ancestral hybridisation events several generations ago. A significant paucity of genetic diversity was found within Anguillan and St Barthélemy I. delicatissima populations, with a single haplotype being identified for each of the three nuclear genes and the mtDNA sequence. This study highlights the urgency for immediate action to conserve Anguilla’s remnant I. delicatissima population. Protection from hybridisation will require translocation to I. iguana -free offshore cays, with supplementary individuals being sourced from neighbouring islands to enhance the genetic diversity of the population.

Climate change decreases the cooling effect from postfire albedo in boreal North America - Stefano Potter; Kylen Solvik; Angela Erb; Scott J. Goetz; Jill F. Johnstone; Michelle C. Mack; James T. Randerson; Miguel O. Román; Crystal L. Schaaf; Merritt R. Turetsky; Sander Veraverbeke; Xanthe J. Walker; et al. (Global Change Biology, 2020)
Fire is a primary disturbance in boreal forests and generates both positive and negative climate forcings. The influence of fire on surface albedo is a predominantly negative forcing in boreal forests, and one of the strongest overall, due to increased snow exposure in the winter and spring months. Albedo forcings are spatially and temporally heterogeneous and depend on a variety of factors related to soils, topography, climate, land cover/vegetation type, successional dynamics, time since fire, season, and fire severity. However, how these variables interact to influence albedo is not well understood, and quantifying these relationships and predicting postfire albedo becomes increasingly important as the climate changes and management frameworks evolve to consider climate impacts. Here we developed a MODIS‐derived ‘blue sky’ albedo product and a novel machine learning modeling framework to predict fire‐driven changes in albedo under historical and future climate scenarios across boreal North America. Converted to radiative forcing (RF), we estimated that fires generate an annual mean cooling of −1.77 ± 1.35 W/m 2 from albedo under historical climate conditions (1971–2000) integrated over 70 years postfire. Increasing postfire albedo along a south–north climatic gradient was offset by a nearly opposite gradient in solar insolation, such that large‐scale spatial patterns in RF were minimal. Our models suggest that climate change will lead to decreases in mean annual postfire albedo, and hence a decreasing strength of the negative RF, a trend dominated by decreased snow cover in spring months. Considering the range of future climate scenarios and model uncertainties, we estimate that for fires burning in the current era (2016) the cooling effect from long‐term postfire albedo will be reduced by 15%–28% due to climate change.

Animal-Borne Telemetry: An Integral Component of the Ocean Observing Toolkit - Rob Harcourt; Ana M. M. Sequeira; Xuelei Zhang; Fabien Roquet; Kosei Komatsu; Michelle Heupel; Clive McMahon; Fred Whoriskey; Mark Meekan; Gemma Carroll; Stephanie Brodie; Colin Simpfendorfer; et al. (Frontiers in Marine Science, 2019)

Genetic diversity and cryptic population re-establishment: management implications for the Bojer’s skink (Gongylomorphus bojerii) - Sarah J. du Plessis; Joanna Howard-McCombe; Zoe E. Melvin; Eleanor C. Sheppard; Isa-Rita M. Russo; Rouben Mootoocurpen; Matt Goetz; Richard P. Young; Nik C. Cole; Michael W. Bruford (Conservation Genetics, 2019)

Spatiotemporal remote sensing of ecosystem change and causation across Alaska - Neal J. Pastick; M. Torre Jorgenson; Scott J. Goetz; Benjamin M. Jones; Bruce K. Wylie; Burke J. Minsley; Hélène Genet; Joseph F. Knight; David K. Swanson; Janet C. Jorgenson (Global Change Biology, 2019)
Contemporary climate change in Alaska has resulted in amplified rates of press and pulse disturbances that drive ecosystem change with significant consequences for socio‐environmental systems. Despite the vulnerability of Arctic and boreal landscapes to change, little has been done to characterize landscape change and associated drivers across northern high‐latitude ecosystems. Here we characterize the historical sensitivity of Alaska's ecosystems to environmental change and anthropogenic disturbances using expert knowledge, remote sensing data, and spatiotemporal analyses and modeling. Time‐series analysis of moderate—and high‐resolution imagery was used to characterize land‐ and water‐surface dynamics across Alaska. Some 430,000 interpretations of ecological and geomorphological change were made using historical air photos and satellite imagery, and corroborate land‐surface greening, browning, and wetness/moisture trend parameters derived from peak‐growing season Landsat imagery acquired from 1984 to 2015. The time series of change metrics, together with climatic data and maps of landscape characteristics, were incorporated into a modeling framework for mapping and understanding of drivers of change throughout Alaska. According to our analysis, approximately 13% (~174,000 ± 8700 km 2 ) of Alaska has experienced directional change in the last 32 years (±95% confidence intervals). At the ecoregions level, substantial increases in remotely sensed vegetation productivity were most pronounced in western and northern foothills of Alaska, which is explained by vegetation growth associated with increasing air temperatures. Significant browning trends were largely the result of recent wildfires in interior Alaska, but browning trends are also driven by increases in evaporative demand and surface‐water gains that have predominately occurred over warming permafrost landscapes. Increased rates of photosynthetic activity are associated with stabilization and recovery processes following wildfire, timber harvesting, insect damage, thermokarst, glacial retreat, and lake infilling and drainage events. Our results fill a critical gap in the understanding of historical and potential future trajectories of change in northern high‐latitude regions.

Traditional plant functional groups explain variation in economic but not size‐related traits across the tundra biome - H. J. D. Thomas; I. H. Myers‐Smith; A. D. Bjorkman; S. C. Elmendorf; D. Blok; J. H. C. Cornelissen; B. C. Forbes; R. D. Hollister; S. Normand; J. S. Prevéy; C. Rixen; G. Schaepman‐Strub; et al. (Global Ecology and Biogeography, 2019)
Aim Plant functional groups are widely used in community ecology and earth system modelling to describe trait variation within and across plant communities. However, this approach rests on the assumption that functional groups explain a large proportion of trait variation among species. We test whether four commonly used plant functional groups represent variation in six ecologically important plant traits. Location Tundra biome. Time period Data collected between 1964 and 2016. Major taxa studied 295 tundra vascular plant species. Methods We compiled a database of six plant traits (plant height, leaf area, specific leaf area, leaf dry matter content, leaf nitrogen, seed mass) for tundra species. We examined the variation in species‐level trait expression explained by four traditional functional groups (evergreen shrubs, deciduous shrubs, graminoids, forbs), and whether variation explained was dependent upon the traits included in analysis. We further compared the explanatory power and species composition of functional groups to alternative classifications generated using post hoc clustering of species‐level traits. Results Traditional functional groups explained significant differences in trait expression, particularly amongst traits associated with resource economics, which were consistent across sites and at the biome scale. However, functional groups explained 19% of overall trait variation and poorly represented differences in traits associated with plant size. Post hoc classification of species did not correspond well with traditional functional groups, and explained twice as much variation in species‐level trait expression. Main conclusions Traditional functional groups only coarsely represent variation in well‐measured traits within tundra plant communities, and better explain resource economic traits than size‐related traits. We recommend caution when using functional group approaches to predict tundra vegetation change, or ecosystem functions relating to plant size, such as albedo or carbon storage. We argue that alternative classifications or direct use of specific plant traits could provide new insights for ecological prediction and modelling.

Cross‐scale controls on carbon emissions from boreal forest megafires - Xanthe J. Walker; Brendan M. Rogers; Jennifer L. Baltzer; Steven G. Cumming; Nicola J. Day; Scott J. Goetz; Jill F. Johnstone; Edward A. G. Schuur; Merritt R. Turetsky; Michelle C. Mack (Global Change Biology, 2018)
Climate warming and drying is associated with increased wildfire disturbance and the emergence of megafires in North American boreal forests. Changes to the fire regime are expected to strongly increase combustion emissions of carbon (C) which could alter regional C balance and positively feedback to climate warming. In order to accurately estimate C emissions and thereby better predict future climate feedbacks, there is a need to understand the major sources of heterogeneity that impact C emissions at different scales. Here, we examined 211 field plots in boreal forests dominated by black spruce ( Picea mariana ) or jack pine ( Pinus banksiana ) of the Northwest Territories ( NWT ), Canada after an unprecedentedly large area burned in 2014. We assessed both aboveground and soil organic layer ( SOL ) combustion, with the goal of determining the major drivers in total C emissions, as well as to develop a high spatial resolution model to scale emissions in a relatively understudied region of the boreal forest. On average, 3.35 kg C m −2 was combusted and almost 90% of this was from SOL combustion. Our results indicate that black spruce stands located at landscape positions with intermediate drainage contribute the most to C emissions. Indices associated with fire weather and date of burn did not impact emissions, which we attribute to the extreme fire weather over a short period of time. Using these results, we estimated a total of 94.3 Tg C emitted from 2.85 Mha of burned area across the entire 2014 NWT fire complex, which offsets almost 50% of mean annual net ecosystem production in terrestrial ecosystems of Canada. Our study also highlights the need for fine‐scale estimates of burned area that represent small water bodies and regionally specific calibrations of combustion that account for spatial heterogeneity in order to accurately model emissions at the continental scale.

Species and Genotype Effects of Bioenergy Crops on Root Production, Carbon and Nitrogen in Temperate Agricultural Soil - Andrew S. Gregory; Jennifer A. J. Dungait; Ian F. Shield; William J. Macalpine; Jennifer Cunniff; Mark Durenkamp; Rodger P. White; Adrian Joynes; Goetz M. Richter (BioEnergy Research, 2018)

Detecting early warning signals of tree mortality in boreal North America using multiscale satellite data - Brendan M. Rogers; Kylen Solvik; Edward H. Hogg; Junchang Ju; Jeffrey G. Masek; Michael Michaelian; Logan T. Berner; Scott J. Goetz (Global Change Biology, 2018)
Increasing tree mortality from global change drivers such as drought and biotic infestations is a widespread phenomenon, including in the boreal zone where climate changes and feedbacks to the Earth system are relatively large. Despite the importance for science and management communities, our ability to forecast tree mortality at landscape to continental scales is limited. However, two independent information streams have the potential to inform and improve mortality forecasts: repeat forest inventories and satellite remote sensing. Time series of tree‐level growth patterns indicate that productivity declines and related temporal dynamics often precede mortality years to decades before death. Plot‐level productivity, in turn, has been related to satellite‐based indices such as the Normalized difference vegetation index ( NDVI ). Here we link these two data sources to show that early warning signals of mortality are evident in several NDVI ‐based metrics up to 24 years before death. We focus on two repeat forest inventories and three NDVI products across western boreal North America where productivity and mortality dynamics are influenced by periodic drought. These data sources capture a range of forest conditions and spatial resolution to highlight the sensitivity and limitations of our approach. Overall, results indicate potential to use satellite NDVI for early warning signals of mortality. Relationships are broadly consistent across inventories, species, and spatial resolutions, although the utility of coarse‐scale imagery in the heterogeneous aspen parkland was limited. Longer‐term NDVI data and annually remeasured sites with high mortality levels generate the strongest signals, although we still found robust relationships at sites remeasured at a typical 5 year frequency. The approach and relationships developed here can be used as a basis for improving forest mortality models and monitoring systems.

Early life history connectivity of Antarctic silverfish ( Pleuragramma antarctica ) in the Ross Sea - Cassandra M. Brooks; Jilda Alicia Caccavo; Julian Ashford; Robert Dunbar; Kimberly Goetz; Mario La Mesa; Lorenzo Zane (Fisheries Oceanography, 2018)
A recent population hypothesis for Antarctic silverfish ( Pleuragramma antarctica ), a critical forage species, argued that interactions between life history and circulation associated with glacial trough systems drive circumpolar distributions over the continental shelf. In the Ross Sea, aggregations of eggs and larvae occur under fast ice in Terra Nova Bay, and the hypothesis predicted that dispersing larvae encounter outflow along the western side of Drygalski Trough. The outflow advects larvae towards the shelf‐break, and mixing with trough inflow facilitates return toward the inner shelf. To examine the hypothesis, we compared samples of P. antarctica collected near Coulman Island in the outflow, along Crary Bank in the inflow, and a third set taken over the rest of the Ross Sea. We ruled out misidentification using an innovative genetic validation. Silverfish larvae comprised 99.5% of the catch, and the highest population densities were found in Drygalski Trough. The results provided no evidence to reject the population hypothesis. Abundance indices, back‐calculated hatching dates, length distributions and growth were congruent with a unified early life history in the western Ross Sea, constrained by cryopelagic early stages in Terra Nova Bay. By contrast, a sample in the Bay of Whales revealed much smaller larvae, suggesting either a geographically separate population in the eastern Ross Sea, or westward connectivity with larvae spawned nearby by fish sourced from troughs upstream in the Amundsen Sea. These results illustrate how hypotheses that integrate population structure with life history can provide precise spatial predictions for subsequent testing.

Toxic, invasive treefrog creates evolutionary trap for native gartersnakes - Scott M. Goetz; Craig Guyer; Scott M. Boback; Christina M. Romagosa (Biological Invasions, 2018)

Vulnerability of eastern US tree species to climate change - Brendan M. Rogers; Patrick Jantz; Scott J. Goetz (Global Change Biology, 2017)
Climate change is expected to alter the distribution of tree species because of critical environmental tolerances related to growth, mortality, reproduction, disturbances, and biotic interactions. How this is realized in 21st century remains uncertain, in large part due to limitations on plant migration and the impacts of landscape fragmentation. Understanding these changes is of particular concern for forest management, which requires information at an appropriately fine spatial resolution. Here we provide a framework and application for tree species vulnerability to climate change in the eastern United States that accounts for influential drivers of future distributions. We used species distribution models to project changes in habitat suitability at 800 m for 40 tree species that vary in physiology, range, and environmental niche. We then developed layers of adaptive capacity based on migration potential, forest fragmentation, and propagule pressure. These were combined into metrics of vulnerability, including an overall index and spatially explicit categories designed to inform management. Despite overall favorable changes in suitability, the majority of species and the landscape were considered vulnerable to climate change. Vulnerability was significantly exacerbated by projections of pests and pathogens for some species. Northern and high‐elevation species tended to be the most vulnerable. There were, however, some notable areas of particular resilience, including most of West Virginia. Our approach combines some of the most important considerations for species vulnerability in a straightforward framework, and can be used as a tool for managers to prioritize species, areas, and actions.

Investigating the extent of parallelism in morphological and genomic divergence among lake trout ecotypes in Lake Superior - Alysse Perreault‐Payette; Andrew M. Muir; Frederick Goetz; Charles Perrier; Eric Normandeau; Pascal Sirois; Louis Bernatchez (Molecular Ecology, 2017)
Understanding the emergence of species through the process of ecological speciation is a central question in evolutionary biology which also has implications for conservation and management. Lake trout ( Salvelinus namaycush ) is renowned for the occurrence of different ecotypes linked to resource and habitat use throughout North America. We aimed to unravel the fine genetic structure of the four lake trout ecotypes in Lake Superior. A total of 486 individuals from four sites were genotyped at 6822 filtered SNP s using RAD seq technology. Our results revealed different extent of morphological and genetic differentiation within the different sites. Overall, genetic differentiation was weak but significant and was on average three times higher between sites (mean F ST = 0.016) than between ecotypes within sites (mean F ST = 0.005) indicating higher level of gene flow or a more recent shared ancestor between ecotypes within each site than between populations of the same ecotype. Evidence of divergent selection was also found between ecotypes and/or in association with morphological variation. Outlier loci found in genes related to lipid metabolism and visual acuity were of particular interest in this context of ecotypic divergence. However, we did not find clear indication of parallelism at the genomic level, despite the presence of phenotypic parallelism among some ecotypes from different sampling sites. Overall, the occurrence of different levels of both genomic and phenotypic differentiation between ecotypes within each site with several differentiated loci linked to relevant biological functions supports the presence of a continuum of divergence in lake trout.

Pan‐tropical hinterland forests: mapping minimally disturbed forests - A. Tyukavina; M. C. Hansen; P. V. Potapov; A. M. Krylov; S. J. Goetz (Global Ecology and Biogeography, 2016)
Aim Tropical forest degradation is a significant source of carbon emissions due to selective logging, fragmentation and other disturbance factors. However, methods for mapping and monitoring pan‐tropical forest degradation are still in their infancy. Here we present a new and automated approach to differentiate forests likely to be affected by degradation dynamics from more structurally intact forests, referred to as hinterland forests. Location Pan‐tropical. Methods Inputs required for hinterland forest mapping include the extent of the initial forest cover and subsequent forest cover loss data, in this case global‐scale Landsat‐derived tree cover and stand‐replacement disturbance maps. User‐defined parameters employed to generate the extent and change of hinterland forest include: (1) minimum size of hinterland forest patch, (2) minimum corridor width, (3) distance from disturbance, and (4) extant history. Results Hinterland forest extent was mapped using forest cover loss data from 2000 to 2012 and hinterland forest loss was quantified from 2007 to 2013. Lidar‐modelled forest height data were shown to be different within and outside hinterland forests, demonstrating the biophysical basis of the hinterland concept in discriminating likely degradation. Overall, hinterland forests experienced an 18% decline from 2007 to 2013. Regional variation in hinterland forest extent and loss was high. Data on 2013 pan‐tropical hinterland forest extent can be downloaded from http://glad.geog.umd.edu/hinterland/index.html and viewed online at http://earthenginepartners.appspot.com/science‐2013‐global‐forest . Main conclusions The largest extent of hinterland forests and of hinterland forest loss was found in L atin A merica, followed by A frica and S outheast A sia, respectively. The highest proportional loss of hinterland forest occurred in S outheast Asia, followed by A frica and L atin A merica, respectively. Nearly 95% of all 2013 hinterland forests were found in 17 of the 69 tropical forest countries studied. The extent and loss of hinterland forest can be an input to national monitoring and management programmes focused on forest carbon stocks, biodiversity conservation and other ecosystem services.

Carbon Sequestration by Perennial Energy Crops: Is the Jury Still Out? - Francesco Agostini; Andrew S. Gregory; Goetz M. Richter (BioEnergy Research, 2015)

Do pingers cause stress in fish? An experimental tank study with European sardine, Sardina pilchardus (Walbaum, 1792) (Actinopterygii, Clupeidae), exposed to a 70 kHz dolphin pinger - Sabine Goetz; M. Begoña Santos; José Vingada; Damián Costas Costas; Antonio González Villanueva; Graham John Pierce (Hydrobiologia, 2015)

Ontogenetic changes in embryonic and brain gene expression in progeny produced from migratory and resident O ncorhynchus mykiss - Garrett J. McKinney; Matthew C. Hale; Giles Goetz; Michael Gribskov; Frank P. Thrower; Krista M. Nichols (Molecular Ecology, 2015)
Little information has been gathered regarding the ontogenetic changes that contribute to differentiation between resident and migrant individuals, particularly before the onset of gross morphological and physiological changes in migratory individuals. The aim of this study was to evaluate gene expression during early development in Oncorhynchus mykiss populations with different life histories, in a tissue known to integrate environmental cues to regulate complex developmental processes and behaviours. We sampled offspring produced from migrant and resident parents, collecting whole embryos prior to the beginning of first feeding, and brain tissue at three additional time points over the first year of development. RNA sequencing for 32 individuals generated a reference transcriptome of 30 177 genes that passed count thresholds. Differential gene expression between migrant and resident offspring was observed for 1982 genes. The greatest number of differentially expressed genes occurred at 8 months of age, in the spring a full year before the obvious physiological transformation from stream‐dwelling parr to sea water‐adaptable smolts begins for migrant individuals. Sex and age exhibited considerable effects on differential gene expression between migrants and resident offspring. Differential gene expression was observed in genes previously associated with migration, but also in genes previously unassociated with early life history divergence. Pathway analysis revealed coordinated differential expression in genes related to phototransduction, which could modulate photoperiod responsiveness and variation in circadian rhythms. The role for early differentiation in light sensitivity and biological rhythms is particularly intriguing in understanding early brain processes involved in differentiation of migratory and resident life history types.

Wnt5a, TLR2 and TLR4 are elevated in advanced human atherosclerotic lesions - Ramiro Malgor; Pooja M. Bhatt; Beth A. Connolly; Denise L. Jacoby; Kyle J. Feldmann; Mitchell J. Silver; Masato Nakazawa; Kelly D. McCall; Douglas J. Goetz (Inflammation Research, 2014)

Vegetation controls on northern high latitude snow‐albedo feedback: observations and CMIP 5 model simulations - Michael M. Loranty; Logan T. Berner; Scott J. Goetz; Yufang Jin; James T. Randerson (Global Change Biology, 2014)
The snow‐masking effect of vegetation exerts strong control on albedo in northern high latitude ecosystems. Large‐scale changes in the distribution and stature of vegetation in this region will thus have important feedbacks to climate. The snow‐albedo feedback is controlled largely by the contrast between snow‐covered and snow‐free albedo (Δα), which influences predictions of future warming in coupled climate models, despite being poorly constrained at seasonal and century time scales. Here, we compare satellite observations and coupled climate model representations of albedo and tree cover for the boreal and A rctic region. Our analyses reveal consistent declines in albedo with increasing tree cover, occurring south of latitudinal tree line, that are poorly represented in coupled climate models. Observed relationships between albedo and tree cover differ substantially between snow‐covered and snow‐free periods, and among plant functional type. Tree cover in models varies widely but surprisingly does not correlate well with model albedo. Furthermore, our results demonstrate a relationship between tree cover and snow‐albedo feedback that may be used to accurately constrain high latitude albedo feedbacks in coupled climate models under current and future vegetation distributions.

MRI-Apparent Localized Deformation of the Median Nerve Within the Carpal Tunnel During Functional Hand Loading - Jessica E. Goetz; Nicole M. Kunze; Erin K. Main; Daniel R. Thedens; Thomas E. Baer; Ericka A. Lawler; Thomas D. Brown (Annals of Biomedical Engineering, 2013)

Carbon Accumulation Patterns During Post-Fire Succession in Cajander Larch (Larix cajanderi) Forests of Siberia - Heather D. Alexander; Michelle C. Mack; Scott Goetz; Michael M. Loranty; Pieter S. A. Beck; Kamala Earl; Sergey Zimov; Sergey Davydov; Catharine C. Thompson (Ecosystems, 2012)

Acinetobacter , Aeromonas and Trichococcus populations dominate the microbial community within urban sewer infrastructure - J. L. VandeWalle; G. W. Goetz; S. M. Huse; H. G. Morrison; M. L. Sogin; R. G. Hoffmann; K. Yan; S. L. McLellan (Environmental Microbiology, 2012)
Summary We evaluated the population structure and temporal dynamics of the dominant community members within sewage influent from two wastewater treatment plants (WWTPs) in Milwaukee, WI. We generated > 1.1 M bacterial pyrotag sequences from the V6 hypervariable region of 16S rRNA genes from 38 influent samples and two samples taken upstream in the sanitary sewer system. Only a small fraction of pyrotags from influent samples (∼ 15%) matched sequences from human faecal samples. The faecal components of the sewage samples included enriched pyrotag populations from Lactococcus and Enterobacteriaceae relative to their fractional representation in human faecal samples. In contrast to the large number of distinct pyrotags that represent faecal bacteria such as Lachnospiraceae and Bacteroides , only one or two unique V6 sequences represented Acinetobacter , Aeromonas and Trichococcus , which collectively account for nearly 35% of the total sewage community. Two dominant Acinetobacter V6 pyrotags (designated Acineto tag 1 and Acineto tag 2) fluctuated inversely with a seasonal pattern over a 3‐year period, suggesting two distinct Acinetobacter populations respond differently to ecological forcings in the system. A single nucleotide change in the V6 pyrotags accounted for the difference in these populations and corresponded to two phylogenetically distinct clades based on full‐length sequences. Analysis of wavelet functions, derived from a mathematical model of temporal fluctuations, demonstrated that other abundant sewer associated populations including Trichococcus and Aeromonas had temporal patterns similar to either Acineto tag 1 or Acineto tag 2. Populations with related temporal fluctuations were found to significantly correlate with the same WWTP variables (5‐day BOD, flow, ammonia, total phosphorous and suspended solids). These findings illustrate that small differences in V6 sequences can represent phylogenetically and ecologically distinct taxa. This work provides insight into microbial community composition and dynamics within the defined environment of urban sewer infrastructure.

The best for the guest: high Andean nurse cushions of Azorella madreporica enhance arbuscular mycorrhizal status in associated plant species - M. Angélica Casanova-Katny; Gustavo Adolfo Torres-Mellado; Goetz Palfner; Lohengrin A. Cavieres (Mycorrhiza, 2011)

The impacts and implications of an intensifying fire regime on Alaskan boreal forest composition and albedo - PIETER S. A. BECK; SCOTT J. GOETZ; MICHELLE C. MACK; HEATHER D. ALEXANDER; YUFANG JIN; JAMES T. RANDERSON; M. M. LORANTY (Global Change Biology, 2011)
Climate warming and drying are modifying the fire dynamics of many boreal forests, moving them towards a regime with a higher frequency of extreme fire years characterized by large burns of high severity. Plot‐scale studies indicate that increased burn severity favors the recruitment of deciduous trees in the initial years following fire. Consequently, a set of biophysical effects of burn severity on postfire boreal successional trajectories at decadal timescales have been hypothesized. Prominent among these are a greater cover of deciduous tree species in intermediately aged stands after more severe burning, with associated implications for carbon and energy balances. Here we investigate whether the current vegetation composition of interior Alaska supports this hypothesis. A chronosequence of six decades of vegetation regrowth following fire was created using a database of burn scars, an existing forest biomass map, and maps of albedo and the deciduous fraction of vegetation that we derived from Moderate Resolution Imaging Spectroradiometer (MODIS) satellite imagery. The deciduous fraction map depicted the proportion of aboveground biomass in deciduous vegetation, derived using a RandomForest algorithm trained with field data sets ( n =69, 71% variance explained). Analysis of the difference Normalized Burn Ratio, a remotely sensed index commonly used as an indicator of burn severity, indicated that burn size and ignition date can provide a proxy of burn severity for historical fires. LIDAR remote sensing and a bioclimatic model of evergreen forest distribution were used to further refine the stratification of the current landscape by burn severity. Our results show that since the 1950s, more severely burned areas in interior Alaska have produced a vegetation cohort that is characterized by greater deciduous biomass. We discuss the importance of this shift in vegetation composition due to climate‐induced changes in fire severity for carbon sequestration in forest biomass and surface reflectance (albedo), among other feedbacks to climate.

Scaling an Instantaneous Model of Tundra NEE to the Arctic Landscape - Michael M. Loranty; Scott J. Goetz; Edward B. Rastetter; Adrian V. Rocha; Gaius R. Shaver; Elyn R. Humphreys; Peter M. Lafleur (Ecosystems, 2011)

Terpenes and flavonoids from an Egyptian collection of Cleome droserifolia - Mohamed I. Aboushoer; Hoda M. Fathy; Maged S. Abdel-Kader; Gilles Goetz; Abdallah A. Omar (Natural Product Research, 2010)

No Differences in Soil Carbon Stocks Across the Tree Line in the Peruvian Andes - Michael Zimmermann; Patrick Meir; Miles R. Silman; Anna Fedders; Adam Gibbon; Yadvinder Malhi; Dunia H. Urrego; Mark B. Bush; Kenneth J. Feeley; Karina C. Garcia; Greta C. Dargie; Wiliam R. Farfan; et al. (Ecosystems, 2010)

Land Use Implications of Increased Biomass Production Identified by GIS-Based Suitability and Yield Mapping for Miscanthus in England - Andrew A. Lovett; Gisela M. Sünnenberg; Goetz M. Richter; A. Gordon Dailey; Andrew B. Riche; Angela Karp (BioEnergy Research, 2009)

Development and evaluation of a GFLV inverted repeat construct for genetic transformation of grapevine - Rahma Jardak-Jamoussi; Patrick Winterhagen; Badra Bouamama; Cornelia Dubois; Ahmed Mliki; Thierry Wetzel; Abdelwahed Ghorbel; Goetz M. Reustle (Plant Cell, Tissue and Organ Culture (PCTOC), 2009)

Caveolin-1 in tumor progression: the good, the bad and the ugly - Jacky G. Goetz; Patrick Lajoie; Sam M. Wiseman; Ivan R. Nabi (Cancer and Metastasis Reviews, 2008)

Results of a short study of interactions of cetaceans and longline fisheries in Atlantic waters: environmental correlates of catches and depredation events - Gema Hernandez-Milian; Sabine Goetz; Catuxa Varela-Dopico; José Rodriguez-Gutierrez; Jorge Romón-Olea; José R. Fuertes-Gamundi; Edelmiro Ulloa-Alonso; Nick J. C. Tregenza; Andy Smerdon; Monserrat G. Otero; Vicente Tato; Jianjun Wang; et al. (Hydrobiologia, 2008)

Immunocytochemical and biochemical detection of EMMPRIN in the rat tooth germ: differentiation-dependent co-expression with MMPs and co-localization with caveolin-1 in membrane rafts of dental epithelial cells - W. Schwab; H. Harada; W. Goetz; M. Nowicki; M. Witt; M. Kasper; K. Barth (Histochemistry and Cell Biology, 2007)

Hyperhydration prior to a simulated second day of the 3-day moderate intensity equestrian competition does not cause arterial hypoxemia in Thoroughbred horses - B. S. Tennent-Brown; T. E. Goetz; M. Manohar; A. S. Hassan; D. E. Freeman; J. S. Bundy; M. R. Evans (European Journal of Applied Physiology, 2006)

Response of Nebraska Sand Hills Natural Vegetation to Drought, Fire, Grazing, and Plant Functional Type Shifts as Simulated by the Century Model - Jennifer M. Mangan; Jonathan T. Overpeck; Robert S. Webb; Carol Wessman; Alexander F. H. Goetz (Climatic Change, 2004)

Molecular analysis of two cytochrome P450 monooxygenase genes required for paxilline biosynthesis in Penicillium paxilli, and effects of paxilline intermediates on mammalian maxi-K ion channels - L. K. McMillan; R. L. Carr; C. A. Young; J. W. Astin; R. G. T. Lowe; E. J. Parker; G. B. Jameson; S. C. Finch; C. O. Miles; O. B. McManus; W. A. Schmalhofer; M. L. Garcia; et al. (Molecular Genetics and Genomics, 2003)

Non-Fatal Acute Liver Injury Possibly Related to High-Dose Ciprofloxacin - M. Goetz; P. R. Galle; A. Schwarting (European Journal of Clinical Microbiology & Infectious Diseases, 2003)

Targeting Microparticles to Select Tissue via Radiation-Induced Upregulation of Endothelial Cell Adhesion Molecules - Mohammad F. Kiani; Hong Yuan; Xin Chen; Lee Smith; M. Waleed Gaber; Douglas J. Goetz (Pharmaceutical Research, 2002)

Inhibition of Nitric Oxide Synthase with L-NAME Does Not Increase Lactate Production at Rest or During Short-term High-intensity Exercise in Thoroughbred Horses - M. Manohar; T.E. Goetz; A.S. Hassan; P. Rothenbaum; S. Humphrey (Veterinary Research Communications, 2001)

Ligand Coated Nanosphere Adhesion to E- and P-Selectin under Static and Flow Conditions - Jonathan E. Blackwell; Nilesh M. Dagia; J. Bradley Dickerson; Ellen L. Berg; Douglas J. Goetz (Annals of Biomedical Engineering, 2001)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

The ovarian regulation of ovulation in teleost fish - F.W. Goetz; M. Garczynski (Fish Physiology and Biochemistry, 1997)